The EDUKASI KELOMPOK TANI HUTAN JEMBARAN DESA NOTOG DALAM MITIGASI LAHAN KRITIS MELALUI PERBANYAKAN VEGETASI PENDUKUNG BUDIDAYA Tetragonula biroi - Rahayu, Diana Retna Utarini Suci; Widhiono MZ, Imam; Sari, Lilik Kartika; da Cruz, Marquita Soares B.; Setiawati, Lisa (Universitas Negeri Surabaya, 2025)
Vacant land that is not utilized has the potential to become critical land which can result in landslides, floods, decreased production functions, which can have an impact on the socio-economic impact of local communities. Members of the Jembaran Forest Farmers Group, Notog Village, have the initiative to cultivate Tetragonula biroi, but most of the members do not understand the mechanisms of bee cultivation, especially the availability of flowering vegetation that produces nectar and pollen as a food source and produces resin as a building material for nests. Based on these problems, this community service activity aims to introduce types of flowering vegetation which play a role in supporting the cultivation of T. biroi which can also increase land productivity, as well as mitigate critical land. This vegetation includes Dombeya sp and Xanthostemon sp, both of which are flowering vegetation and can play a role in increasing land productivity, increasing water penetration into the soil, so as to prevent flooding. This service activity method is carried out in three stages, namely 1). Socialization and discussion about the types of flowering vegetation that support the cultivation of T. biroi, 2). Practice planting vegetation as a demonstration plot which is carried out directly, 3) monitoring and evaluation to determine the level of change in participants' mindset with indicators of increasing the amount of flowering vegetation which also acts as a means of mitigating flood disasters and decreasing soil fertility. The results of the activity showed an increase in the participants' knowledge and understanding of the material presented